A Model for Understanding the Role of Sound Perception in Hospital Spaces - Iyendo, Timothy Onosahwo (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2016)
A hospital can be a stressful place, and for patients and health care providers being in a hospital can be an exceedingly distressing experience. Evidence from existing literature has propounded that exploring the positive aspect of sound in a hospital context can evoke positive feelings in both patients and staff. However, the pursuits of visual dimensions of space, and the dominance of intensive acoustic analysis have undermined the notion that sound can positively influence experience in hospital space design. This aspect is often overlooked, as research in architectural practice relies more on aesthetic listening rather than developing a critical listening technique. This suggests that there is a scope for research into the aspects of hospital space experience with a focus on the role of sound as they relate to what may be positive, negative effects and the feelings that different sounds can evoke. This study aims at developing a theoretical framework, a paradigm for noise research and architectural design practice for hospital environments. The intention of this investigation is to move beyond the conception that noise is simply unwelcome and to explore the extent to which investigators have researched into the meaning of sound in the environment of health care indoor spaces. This study is interdisciplinary, taking up the subject that includes theories of sound perception and ecology, empirical studies, evidence-based design theories, environmental psychology, hospital management and multisensory design in architecture, including other environmental factors and hospital experiences. A qualitative content analysis was employed to analyse a vast body of literature retrieved from the Web of Science, PubMed, Scopus, ProQuest Central, MEDLINE, and Google scholar. Additionally, a qualitative research inquiry based on observation, discussion with experts on related field via emails and documentation of studies was used to address the study objectives. These form grounds to derive and develop a conceptual model to serve as a guideline for improving healthcare experience and design practice for hospital spaces. The result of this study pointed out that not all sounds give a negative impression within healthcare soundscapes. The perception of sound was shown to bring about positive change in patient-reported outcomes such as eliciting positive emotion and decreasing the levels of stressful health conditions. The study findings also showed that hospital space designed to incorporate sound, good space qualities, wall openings and access to nature, including appropriate materials and finishes has the potential to impact upon patients and staff health outcomes, thereby reducing stress and improving coping strategies, effectiveness in delivering care, safety, and overall sound quality satisfaction. Therefore, with the support of evidence-based research, conceptualizing the nature of sound in the hospital context as a soundscape, rather than merely noise can permit a subtler and socially useful understanding of the role of sound and music in the hospital setting. This may create a means for improving the hospital experience for patients and patients care teams. This area should be further explored to create a greater understanding of this new paradigm in the field of hospital noise. Keywords: Architectural design, environmental design, hospital experience, music psychology, noise, positive distraction, sound design, sound perception, soundscape, stress reduction.

ÖZ: Hastahaneler son derece stresli bir yer olabilir, hastalar ve personel için stresli bir deneyim oluşturabilir. Literatürde ortaya atılan kanıta göre, bir hastahane ortamındaki sesin pozitif yönünü keşvetmek, hastalar ve personel için olumlu duygular uyandırabilir ancak, alanların görsel boyut takipçiliği ve yoğun akustik hakimiyetin analizi, hastahane alanlarındaki sesin, mekanı olumlu etkileyebileceği fikrini zayıflattı. Mimari uygulamalardaki araştırmalar daha fazla estetik dinlemeyi değerlendirirken, kritik dinleme tekniği göz ardı edildi. Hastahane alanlarında yapılan araştırma kapsamında olumlu ve olumsuz sesin ne olduğuna odaklanıldı ve farklı seslerin nasıl duygular uyandıracağı araştırıldı. Bu çalışmayla birlikte, teorik bilgiye dayanarak ses için yeni bir paradigma oluşturmak ve hastahaneler için yeni bir tasarım denemesi yapmak amaçlanmaktadır. Bu amaçla, gürültünün sadece istenmeyen bir olgu olmadığı kavramı geliştirilip, sağlık alanlarındaki iç mekanlarda sesin anlamının araştırılması hedeflenmektedir. Bu çalışma disiplinlerarası bir çalışma olup ses hakındaki ekolojik, deneysel, kanıt temelli tasarım teorileri, çevresel psikoloji, hastahane yönetimi ve mimarideki çok algılı tasarımla diğer çevresel faktörler ve tecrübeler içermektedir. Bu çalışma kapsamında yapılacak olan nitel araştırma gözlem’e, bu alandakı uzmanlarla email yoluyla tartışmaya ve dökümantasyon çalışmasına dayanmaktadır. Bununla birlikte, nitel araştırmanın içeriği, Web of Science, PubMed, Scopus, ProQuest Central, MEDLINE ve Google scholar aracılığıyla çoğu literatür taraması yapılmıştır. Ses hakkında türetilen tasarım ve konsept çalışmaları bu literatür araştırmasıyla modellenmiş olup konseptsel çerçeve, pozitif ses atmosferinin tasarımı geliştirilerek, hastahaneler için tasarım denemesi yapılmıştır. Sunuç olarak bu çalışma sağlık merkezlerindeki tüm seslerin negatif etki yaratmadığnı göstermiştir. Sesin algılanması, pozitif bir duygu yarattığını ve sağlık merkezlerindeki stresli atmosferin düzeyini azalttığını göstemektedir. Bu çalışma aynı zamanda hastahane alanlarının sesi birleştirmek, iyi alan kalitesi, duvar açıklıkları, doğayla bir erişim bağlantısı kurmak için, tasarlandığını göstermektedir. Uygun malzeme ve kaplama hastaların ve personelin algısını etkileme potansiyeline sahip olup, stresi azaltma ve başa çıkma stratejileri geliştirmede yardımcıdır. Bakım, güvenlik ve genel ses kalitesi memnuniyeti, hastalar ve çalışanlar üzerindeki etkiyi etkilemektedir. Bununla birlikte, kanıt odaklı araştırma, hastahane bağlamındaki ses atmosferinde, doğadaki sesi kavramsallaştırma yerine, hastahane ortamındaki sesin ve müziğin rolü üzerinde incelikli ve topluma yararlı bir anlayışa izin verebileceğini göstermiştir. Bu da, hastalar ve çalışanlar için daha iyi bir atmosferin yaratılabileceğni göstermiştir. Bu alan ayrıca hastahanedeki seslerle ilgili alandaki bu yeni paradigmayı dahada geliştirmek için araştırılmalıdır.
Doctor of Philosophy in Architecture. Thesis (Ph.D.)--Eastern Mediterranean University, Faculty of Architecture, Dept. of Architecture, 2016. Supervisor: Assoc. Prof. Dr. Rafooneh M. Sani.
Keywords: Architecture; Architectural design; environmental design; hospital experience; music psychology; noise; positive distraction; sound design; sound perception; soundscape; stress reduction